Ballet Klauss Vianna in Belo Horizonte (1958-1962): paths of a modernity for the Brazilian ballet - Alvarenga, Arnaldo Leite de (Revista Brasileira de Estudos da Presença, 2021)
The article seeks to discuss four choreographic creations by Klauss Vianna, between the years 1958 and 1962, when elaborating his own modern aesthetic for Brazilian ballet. Methodologically, images from 4 covers of programs by Ballet Klauss Vianna (BKV), photographs from 4 works that were part of these programs, oral testimonies, articles and journalistic criticism of the time, writings by Vianna, authors linked to Nouvelle Histoire, to Art criticism, among others, relating them. It is intended to highlight the potential of images as a relevant methodological tool for a possible understanding of the choreographic productions of Klauss Vianna in the dance historiography in Brazil.